La production animale au Mali central: engraissement des ovins en petite exploitation, le "mouton de case" - Kolff, H.E.; Wilson, R.T. (CIPEA, 1983)
Describes & analyses the "Mouton de Case" small scale sheep fattening system of Central Mali, with particular reference to ownership of sheep & extent of practice in the agro-pastoral & rainfed farming subsystems, relation between ownership of other livestock and keeping of "Mouton de Case"; management practices, feeding systems & feeds; costs & benefits, motivation & constraints, and offtake & price/weight/age relationships.